2022
DOI: 10.1021/acs.inorgchem.2c03805
|View full text |Cite
|
Sign up to set email alerts
|

Improved Catalytic Activity and Stability of Co9S8 by Se Incorporation for Efficient Oxygen Evolution Reaction

Abstract: Combining an excellent electrocatalytic activity with the good structural stability of Co9S8 remains challenging for the oxygen evolution reaction (OER). In this study, density functional theory was used to demonstrate the importance of moderate adsorption strength with *O and *OOH intermediate species on Co9S8 for achieving excellent electrocatalytic performances. A novel strategy was proposed to effectively optimize the *O oxidation to *OOH by introducing Se heteroatoms to adjust adsorption of the two interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…It should be noted that S-Co 9 S 8 possesses a higher proportion of Co 2+ /Co 3+ , which is beneficial for the formation of a true active phase during the electrochemical OER processes and can effectively improve the OER performance. 35 In the high-resolution S 2p spectra, both S-Co 9 S 8 and H-Co 9 S 8 represent the characteristic peaks of Co–S at about 161.71 and 162.80 eV. Additionally, the peak at the 164.2 eV can be assigned to the surface sulfide ions of the materials, and the existence of SO 4 2− indicated that they were partly oxidized by air.…”
Section: Resultsmentioning
confidence: 93%
“…It should be noted that S-Co 9 S 8 possesses a higher proportion of Co 2+ /Co 3+ , which is beneficial for the formation of a true active phase during the electrochemical OER processes and can effectively improve the OER performance. 35 In the high-resolution S 2p spectra, both S-Co 9 S 8 and H-Co 9 S 8 represent the characteristic peaks of Co–S at about 161.71 and 162.80 eV. Additionally, the peak at the 164.2 eV can be assigned to the surface sulfide ions of the materials, and the existence of SO 4 2− indicated that they were partly oxidized by air.…”
Section: Resultsmentioning
confidence: 93%
“…17 found that the doping of Se could reduce the energy barrier for the rate-determining step in the OER process, which promotes the adsorption of *OOH and improves the electrocatalytic activity for water splitting. 18 On the other hand, vacancy defects have also been proven to be an effective method for altering interfacial chemical properties and exposing active sites. 19,20 Qian et al combined heterostructure engineering and vacancy strategies to fabricate a CoP v -Mo x P v /CNT electrocatalyst enriched with P defects and indicated that P vacancies can promote reaction kinetics and generate more active sites, ultimately displaying an overpotential of only 138 mV at 10 mA cm −2 for HER in 0.5 M H 2 SO 4 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…For instance, Yang et al employed both heteroatom doping and heterostructure engineering to prepare W-CoP/FeP nanoparticles and revealed that W-doping provides additional active sites, accelerates electron transfer rates, and enhances the synergistic effect between CoP and FeP . Wang et al prepared Se-doped Co 9 S 8 electrodes and found that the doping of Se could reduce the energy barrier for the rate-determining step in the OER process, which promotes the adsorption of *OOH and improves the electrocatalytic activity for water splitting …”
Section: Introductionmentioning
confidence: 99%
“…However, these energy sources are intermittent in their availability. To ensure a continuous energy supply, there is an urgent need to develop efficient energy storage devices [4,5] . Supercapacitors have the potential to serve as an alternative electrochemical energy storage technology, replacing widely commercialized rechargeable batteries [3,6,7] .…”
Section: Introductionmentioning
confidence: 99%